2015
DOI: 10.18103/mra.v0i3.204
|View full text |Cite
|
Sign up to set email alerts
|

Health of mothers of children with intellectual disability or autism spectrum disorder: a review of the literature

Abstract: Background:The deficits associated with intellectual disability (ID) and autism spectrum disorder (ASD) place a burden on their co-residing families which may impact maternal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 55 publications
3
18
0
2
Order By: Relevance
“…In addition, compared with parents of neuro-typical children, caregivers' levels of anxiety and depression were found to be more likely to satisfy criterion for clinical mood disorder (Gallagher, Phillips, Oliver, & Carroll, 2008). That caregiving stress is associated with poorer psychological functioning was also demonstrated in two recent meta analyses (Easter, Sharpe, & Hunt, 2015;Hayes & Watson, 2013) and review studies (Cousino & Hazen, 2013;Fairthorne, de Klerk, & Leonard, 2015). The stress of caring for a child with a DD has also been linked with alterations in a variety of health relevant, physiological parameters.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, compared with parents of neuro-typical children, caregivers' levels of anxiety and depression were found to be more likely to satisfy criterion for clinical mood disorder (Gallagher, Phillips, Oliver, & Carroll, 2008). That caregiving stress is associated with poorer psychological functioning was also demonstrated in two recent meta analyses (Easter, Sharpe, & Hunt, 2015;Hayes & Watson, 2013) and review studies (Cousino & Hazen, 2013;Fairthorne, de Klerk, & Leonard, 2015). The stress of caring for a child with a DD has also been linked with alterations in a variety of health relevant, physiological parameters.…”
Section: Introductionmentioning
confidence: 92%
“…From the perspective of mothers, experiences are often positive (Horsley & Oliver, ). However, some report anxiety and distress, lack of partner support, loss of employment with financial consequences, and ability to respond effectively to the needs of siblings (Fairthorne, De Klerk, & Leonard, ). While there has been a focus on families and mothers, there has been less attention on the issues and concerns experienced by fathers of children with ID, an assertion made by Hornby in in a review and analysis concerning fathers of children with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous review [12], we found that mothers of children with Down syndrome generally had better health than mothers of children with other intellectual disabilities. In turn, mothers of children with intellectual disabilities other than Down syndrome, generally had better health than mothers of children with ASD [especially ASD without ID] (Figure 1).…”
Section: Maternal Health By the Child's Diagnosis Or Sub-type And Thementioning
confidence: 85%
“…For example, using linked data, we demonstrated that in the years after their child's birth, mothers of children with ASD or ID had higher rates of psychiatric disorders than other mothers [9,10]. Furthermore, we also identified health differentials in mothers of children with different sub-types of ASD or ID [12]. Using the12 Item Short Form Health Survey (SF-12), parents of children with ASD without ID were also reported as experiencing lower QoL and more stress than parents of children with ASD with ID [7].…”
Section: Introductionmentioning
confidence: 86%